PENINGKATAN HASIL BELAJAR SISWA KELAS VI SD NEGERI KARANGGONDANG MATERI DEBIT MENGGUNAKAN ALAT PERAGA KONSAPALUIS - Jiman, Jiman Jiman (Satya Widya, 2022)
The purpose of this study was to determine the increase in learning outcomes of grade VI students of SD Negeri Karanggondang for the 2019/2020 academic year on discharge material with the help of consapaulist teaching aids. This research is a classroom action research which consists of 4 stages, namely planning, implementation, observation and reflection. Data collection techniques using observation sheets, learning outcomes tests and documentation. The data analysis technique is descriptive analysis. The results showed that there was an increase in student learning outcomes with the help of konsapaluis teaching aids on discharge material. The increase in learning outcomes can be seen in the completeness of learning outcomes and the average score of students. In the first cycle of learning completeness 31.81%. While the average learning outcomes of the first cycle is 59.55. In the second cycle, there was an increase in the mastery of learning outcomes that reached 86.37%. An increase also occurred for the average learning outcomes of the second cycle of 82.27.